Comparing Print and eBook Usage to Meet Patron Needs. Issue 2 (3rd April 2021) - Wilson, Kelly Marie; Hooper, R.; Simpson, J.; Slay, J.
Abstract: Over the past two decades the availability of eBooks to library users has increased exponentially despite continued financial challenges. In this study, four librarians examined eBook and print book usage to determine the best way to allocate collection funds. After determining which subjects were being used, the researchers surveyed students across all campuses and sites to discover the users' preferences for, and knowledge of, the library's collections. The study resulted in an improved distribution of funds and insight into what could be better emphasized in bibliographic instruction sessions.